2002
DOI: 10.1128/aac.46.8.2387-2392.2002
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Pharmacokinetics of Lamivudine in Human Immunodeficiency Virus-Infected Patients with End-Stage Renal Disease Receiving Chronic Dialysis

Abstract: The steady-state pharmacokinetics of lamivudine were evaluated in 11 subjects with human immunodeficiency virus infection and end-stage renal disease, 9 of whom were receiving hemodialysis and 2 of whom were receiving chronic ambulatory peritoneal dialysis (CAPD). All subjects received 150 mg of lamivudine daily for at least 2 weeks prior to sampling for determination of the pharmacokinetics of lamivudine over a 24-h period on 2 consecutive days. On the first day, subjects received 150 mg of oral lamivudine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…However, because lamivudine has a large volume of distribution, the amount of drug removed during dialysis is small compared with the total pool. Therefore, dialysis per se appears to have little impact on the overall dosing regimen, although dosing after hemodialysis is advisable 70 …”
Section: Treatment Of Hepatitis B Virus‐related Hepatic Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because lamivudine has a large volume of distribution, the amount of drug removed during dialysis is small compared with the total pool. Therefore, dialysis per se appears to have little impact on the overall dosing regimen, although dosing after hemodialysis is advisable 70 …”
Section: Treatment Of Hepatitis B Virus‐related Hepatic Complicationsmentioning
confidence: 99%
“…Therefore, dialysis per se appears to have little impact on the overall dosing regimen, although dosing after hemodialysis is advisable. 70 In contrast, despite the recommendation on dose adjustment for renal insufficiency, it has been reported that a dosage grossly higher than the recommended renal dose can still be well tolerated in dialysis patients. In the report, hemodialysis patients with HIV infection were treated with lamivudine 150 mg daily, sixfold the recommended renal dose, and yet no obvious adverse effects were observed after several months of treatment.…”
Section: Lamivudinementioning
confidence: 99%
See 1 more Smart Citation
“…1 However, in practice, many clinicians take advantage of 3TC's wide therapeutic index, as well as its favorable side effect profile and prescribe higher than recommended doses (up to the standard daily dose of 300 mg) in patients with renal impairment. [2][3][4][5] This allows for decreased pill burden and, consequently, regimen simplification. Clinicians may have embraced this practice in the hope of avoiding the use of 3TC oral solution, typically required to achieve the recommended dose adjustment for HD.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, pharmacokinetic modeling in patients undergoing long-term dialysis (hemodialysis and CAPD) has suggested that the amount of lamivudine removed by dialysis is small compared with the total body pool of lamivudine. 36 Hence, in patients undergoing long-term dialysis, a lamivudine dosage of 25 mg/day (given after dialysis on the day of hemodialysis) will likely provide sufficient concentration of the drug. Lamivudine is often given as a 150-mg dose after each dialysis session for patients undergoing hemodialysis, but no data exist to support the use of this dose in end-stage renal disease.…”
Section: Lamivudinementioning
confidence: 99%